Composite flame-retardant fabric and preparation method thereof
By performing in-situ deposition of nanosilicon dioxide and nanoalumina on the fiber surface and combined with silane coupling agent modification, the problem that existing flame retardant fabrics are difficult to combine flame retardant, UV resistance and passive radiation refrigeration functions are solved, and the multifunctional integration and efficient performance of the fabric are achieved.
Patent Information
- Application Number
- CN202411698207.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
Existing flame-retardant fabrics are difficult to have both flame retardant, anti-ultraviolet rays and passive radiation refrigeration functions, especially in high temperature environments that cannot effectively protect the human body.
By performing in-situ deposition of nanosilicon dioxide and nanoalumina on the fiber surface and modifying with silane coupling agent, the flame retardant properties, ultraviolet resistance and cooling effect of the fiber are enhanced.
It realizes the integration of multiple functions of fabrics, has excellent flame retardant performance, anti-ultraviolet function and passive radiation refrigeration effect, significantly improving the practicality of the material and the wide range of application scenarios.
Smart Images

Figure CN119593129A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a composite flame-retardant fabric and a preparation method thereof, and belongs to the fields of textile engineering and material science. Background Art
[0002] With the intensification of global climate change and the increasing number of high-temperature working environments and outdoor activities, people's demand for functional textile materials is rapidly increasing. In particular, in the fields of fire-resistant clothing, outdoor protective equipment and building materials, composite materials with multiple functions are gaining more and more attention. These functions include not only flame retardancy, but also UV protection, thermal management and comfort.
[0003] Traditional flame-retardant fabrics often rely on adding chemical flame retardants or using high-temperature resistant fibers to achieve flame retardant effects. However, such fabrics can usually only meet single functional requirements, such as flame retardancy or high-temperature resistance, and cannot have both UV resistance and thermal management properties. Especially in high-temperature environments, the human body needs to reduce heat accumulation through effective heat radiation or heat dissipation. At the same time, with the increase in outdoor activities, the UV resistance of fabrics has become crucial, and the problems of UV damage to the skin and fabric aging need to be solved urgently.
[0004] In recent years, the rapid development of nanotechnology has provided a new direction for the preparation of multifunctional composite materials. Nanomaterials have unique optical, thermal and chemical properties, which can significantly improve the comprehensive performance of materials. For example, nano-silicon dioxide can effectively absorb ultraviolet rays, thus giving fabrics anti-ultraviolet functions, while nano-aluminum oxide has a high infrared reflectivity, which can reduce the absorption of infrared rays by the human body and achieve the effect of passive radiation cooling. This makes the application of nanomaterials in the textile field have broad prospects.
[0005] However, how to effectively combine the three functions of flame retardancy, UV resistance and passive radiation cooling is still a technical problem in the current field of textile materials. The present invention aims to develop a composite fabric with multiple functions by introducing surface modification technology of nano-silicon dioxide and nano-alumina and combining silane coupling agent to further improve the stability and durability of the material, so as to meet the market demand for high-performance functional textiles. Summary of the invention
[0006] The present invention provides a composite flame-retardant fabric and a preparation method thereof. The fabric has good mechanical strength, thermal stability and multifunctional performance by in-situ deposition of nano-silicon dioxide and nano-aluminum oxide on the fiber surface and combined with silane coupling agent modification. The fabric is particularly suitable for high temperature protection, outdoor activities and special working environments, meeting users' needs for high-performance and multifunctional textile materials.
[0007] The composite flame-retardant fabric of the present invention is composed of modified fiber, polyester fiber, viscose fiber, nylon fiber and carbon fiber. The modified fiber is surface-modified by nano-silicon dioxide and nano-alumina, which improves the flame retardant performance, anti-ultraviolet performance and cooling effect of the fabric. Nano-silicon dioxide has the function of absorbing ultraviolet rays, effectively protecting the skin from ultraviolet damage and delaying the aging of textiles; nano-alumina has a high infrared reflectivity, realizes passive radiation cooling by reflecting infrared rays, and avoids heat absorption and temperature rise of the human body.
[0008] The preparation method of the present invention comprises a series of processing steps, including fiber degreasing, surface activation, plasma treatment, in-situ growth of nano-silicon dioxide and nano-alumina, and surface modification of a silane coupling agent. The method increases the chemical activity of the fiber surface by plasma treatment, then deposits nano-silicon dioxide and nano-alumina, and further modifies the surface by a silane coupling agent, thereby enhancing the bonding force between the fiber and the nanoparticles and the stability of the material.
[0009] To achieve the purpose of the invention, the technical solution adopted by the present invention is: a composite flame-retardant fabric, which is composed of 40 to 60 parts of modified fiber, 30 to 40 parts of polyester fiber, 15 to 20 parts of viscose fiber, 15 to 20 parts of nylon fiber, and 20 to 30 parts of carbon fiber in terms of weight; the preparation method of the modified fiber specifically includes the following steps:
[0010] S1: Add 1-2L of deionized water into a container, and mix 0.3-0.5% household detergent and 10-15% ethanol to form a uniform degreasing solution; immerse the cotton fiber in the degreasing solution at 50-60°C, stir at a speed of 150-200rpm for 30-60 minutes, take out and dry at 60-80°C for 1-2 hours;
[0011] S2: Take another container, add 1-2L of deionized water, mix 1-2% ammonia water and 0.5-2% hydrogen peroxide to form a surface activation solution, immerse the degreased fiber in it and heat it to 40-50°C, put the beaker into an ultrasonic cleaning machine, and perform ultrasonic treatment at a frequency of 40-50kHz for 10-15 minutes; after taking it out, rinse it in deionized water for 2-3 times, each time for 5-10 minutes to remove residual chemicals, and then dry the activated fiber at 70-80°C for 1-2 hours to ensure that the fiber surface is completely dry and activated;
[0012] S3: placing the cleaned and dried fiber substrate into the vacuum chamber of the plasma treatment equipment to ensure that the fibers are evenly distributed and do not overlap; starting the vacuum system, reducing the pressure in the vacuum chamber to 1-13 Pa, introducing oxygen into the vacuum chamber with a gas flow rate of 10-100 cubic centimeters per minute; starting the plasma generator with a power of 10-100w, and treating for 5-20 minutes to increase the chemical activity of the fiber surface;
[0013] S4: dissolving tetraethoxysilane in ethanol at a concentration of 2-5%, sequentially adding 1-2L of deionized water, 1-3% ammonia water, and the fiber treated in S3, stirring the solution for 30-60 minutes, filtering, collecting the fiber, and drying the fiber at 40-50° C. to obtain nano-silica modified fiber;
[0014] S5: dissolving aluminum nitrate in water to a concentration of 2-5%, adding nano-silicon dioxide modified fiber to the solution, heating the solution to 50-60° C., and stirring continuously to promote the hydrolysis of aluminum ions. After reacting for 1-3 hours, filtering, collecting the fiber, and drying the fiber at 40-50° C. to obtain nano-alumina modified fiber;
[0015] S6: 0.5-1% of silane coupling agent is dissolved in anhydrous ethanol, and a pH adjuster is added to adjust the pH to 4-5 to promote the hydrolysis and reaction of silane; the fiber that has undergone in-situ growth treatment is placed in the silane coupling agent solution to ensure that the fiber is completely immersed, and the temperature is controlled at 40-50° C. to soak for 12-24 hours; after soaking, the fiber is taken out and rinsed with plasma water to remove the residual silane coupling agent, and cured at 120-150° C. for 12-24 hours to enhance the chemical bonding between the silane coupling agent and the nano-silica to obtain a modified fiber.
[0016] According to a composite flame-retardant fabric, the nano-silica particle size on the surface of the nano-silica modified fiber described in S4 is 10 to 50 nanometers.
[0017] According to a composite flame-retardant fabric, the particle size of the nano-alumina on the surface of the nano-alumina modified fiber described in S5 is 10 to 30 nanometers.
[0018] According to a composite flame-retardant fabric, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0019] According to a composite flame-retardant fabric, the pH regulator is acetic acid.
[0020] According to a composite flame-retardant fabric, a method for preparing the composite flame-retardant fabric is as follows:
[0021] S1 weighs the modified fiber, polyester fiber, viscose fiber, nylon fiber and carbon fiber respectively according to the formula ratio, adds the weighed fibers into the high-speed mixer in turn, and stirs them for 5 to 10 minutes by mechanical stirring to ensure that the fibers are initially evenly distributed;
[0022] S2 performs secondary mixing of the preliminarily mixed fibers through a cotton opener for 15 to 30 minutes;
[0023] The mixed fibers of S3 can be treated with slight pressure to form a shaped fiber sheet, which is convenient for subsequent processing;
[0024] S4 stores the shaped fibers in a dry environment to avoid moisture or contamination to ensure the stability of fiber performance.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) Multifunctional integration: The patented fabric has flame retardant, UV resistance and passive radiation cooling functions, which can provide all-round protection in high temperature environments, significantly improving the practicality of the material and the breadth of application scenarios.
[0027] (2) Excellent flame retardant properties: Through the modification of nano-silicon dioxide and nano-alumina, this fabric has excellent flame retardant properties, which can effectively prevent the spread of flames and oxygen contact, protecting the wearer from fire hazards.
[0028] (3) Anti-ultraviolet function: The introduction of nano-silica enhances the anti-ultraviolet performance of the fabric, which can effectively absorb ultraviolet rays, prevent ultraviolet rays from damaging the skin, and delay the aging of textile materials.
[0029] (4) High structural stability: Modification with silane coupling agent significantly improves the mechanical strength and chemical resistance of the fabric, ensuring a stronger bond between the nanoparticles and the fibers, thus extending the service life of the fabric.
[0030] (5) Passive radiation cooling effect: The high infrared reflectivity of nano-alumina effectively prevents infrared absorption, provides a passive cooling effect, reduces the rise in human body temperature, and improves the wearer's comfort in high temperature environments.
[0031] Instruction Manual
[0032] Figure 1 , 3 5 is a scanning electron microscope image of Examples 1, 2 and 3 before modification with silane coupling agent;
[0033] Figure 2 , 4 6 are scanning electron microscope images of Examples 1, 2 and 3 after modification with silane coupling agent;
[0034] Figure 7 The ultraviolet transmittance trend diagram of the fibers obtained in Examples 1, 2, and 3 compared with common commercially available fabrics; DETAILED DESCRIPTION
[0035] Embodiment 1
[0036] Add 1L of deionized water to a container, and mix 0.3% household detergent and 10% ethanol to form a uniform degreasing solution; immerse the cotton fiber in the degreasing solution at 50°C, stir at 150rpm for 30 minutes, and take it out and dry it at 60°C for 1 hour. Take another container and add 1L of deionized water, mix 1% ammonia water and 0.5% hydrogen peroxide to form a surface activation solution, immerse the degreased fiber in it and heat it to 40-50°C, put the beaker into an ultrasonic cleaning machine, and perform ultrasonic treatment at a frequency of 40kHz for 10-15 minutes; after taking it out, rinse it in deionized water twice, 5 minutes each time, to remove residual chemicals, and then dry the activated fiber at 70°C for 1 hour to ensure that the fiber surface is completely dry and activated. Place the cleaned and dried fiber substrate into the vacuum chamber of the plasma treatment equipment to ensure that the fibers are evenly distributed and not overlapped; start the vacuum system, reduce the pressure in the vacuum chamber to 1Pa, introduce oxygen into the vacuum chamber, and the gas flow rate is 10 cubic centimeters / minute; start the plasma generator with a power of 10w and treat for 5 minutes to increase the chemical activity of the fiber surface. Take tetraethoxysilane and dissolve it in ethanol at a concentration of 2%, add 1L deionized water, 1% ammonia water, and S3 treated fiber in sequence, stir the solution for 30 minutes, filter, collect the fiber, and dry the fiber at 40°C to obtain nano-silica modified fiber. Take aluminum nitrate and dissolve it in water at a concentration of 2%, then add nano-silica modified fiber to the solution, heat the solution to 50°C, and stir continuously to promote the hydrolysis of aluminum ions. After reacting for 1 hour, filter, collect the fiber, and dry the fiber at 40°C to obtain nano-alumina modified fiber. Take 0.5% of the silane coupling agent and dissolve it in anhydrous ethanol, add a pH adjuster to adjust the pH to 4 to promote the hydrolysis and reaction of silane; put the fiber that has been treated with in-situ growth into the silane coupling agent solution to ensure that the fiber is completely immersed, and control the temperature at 40°C to soak for 12 hours; after soaking, take out the fiber and rinse it with plasma water to remove the residual silane coupling agent, and cure it at 120°C for 12 hours to enhance the chemical bonding between the silane coupling agent and nano-silica to obtain modified fibers. The fibers before and after modification with the silane coupling agent were characterized by scanning electron microscopy, and the test results are as follows: Figure 1 , 2 As shown, the silane coupling agent can form a strong chemical bond between the nanoparticles and the fiber surface, increase their binding force, prevent the nanoparticles from falling off, and improve durability.
[0037] Embodiment 2
[0038] Add 1L of deionized water to a container, and mix 0.3-0.5% household detergent and 13% ethanol to form a uniform degreasing solution; immerse the cotton fiber in the degreasing solution at 55°C, stir at 180rpm for 45 minutes, and take it out and dry it at 70°C for 1.5 hours. Take another container and add 1.5L of deionized water, mix 1.5% ammonia water and 1% hydrogen peroxide to form a surface activation solution, immerse the degreased fiber in it and heat it to 45°C, put the beaker into an ultrasonic cleaning machine, and perform ultrasonic treatment at a frequency of 45kHz for 13 minutes; after taking it out, rinse it in deionized water 3 times, 8 minutes each time, to remove residual chemicals, and then dry the activated fiber at 75°C for 1.5 hours to ensure that the fiber surface is completely dry and activated. Place the cleaned and dried fiber substrate into the vacuum chamber of the plasma treatment equipment to ensure that the fibers are evenly distributed and not overlapped; start the vacuum system, reduce the pressure in the vacuum chamber to 6Pa, introduce oxygen into the vacuum chamber, and the gas flow rate is 50 cubic centimeters / minute; start the plasma generator with a power of 50w, and treat for 10 minutes to increase the chemical activity of the fiber surface. Take tetraethoxysilane and dissolve it in ethanol at a concentration of 4%, add 1.5L deionized water, 2% ammonia water, and S3 treated fiber in sequence, stir the solution for 45 minutes, filter, collect the fiber, and dry the fiber at 45°C to obtain nano-silica modified fiber. Take aluminum nitrate and dissolve it in water at a concentration of 4%, then add nano-silica modified fiber to the solution, heat the solution to 55°C, and stir continuously to promote the hydrolysis of aluminum ions. After reacting for 2 hours, filter, collect the fiber, and dry the fiber at 45°C to obtain nano-alumina modified fiber. Take 0.8% of silane coupling agent and dissolve it in anhydrous ethanol, add pH regulator to adjust pH to 4 to promote the hydrolysis and reaction of silane; put the fiber after in-situ growth treatment into the silane coupling agent solution to ensure that the fiber is completely immersed, and control the temperature at 45°C to soak for 18 hours; after soaking, take out the fiber and rinse it with plasma water to remove the residual silane coupling agent, and cure it at 135°C for 18 hours to enhance the chemical bonding between the silane coupling agent and nano-silica to obtain modified fiber. The fiber before and after modification with silane coupling agent was characterized by scanning electron microscope, and the test results are as follows: Figure 3 , 4 As shown, the silane coupling agent can form a strong chemical bond between the nanoparticles and the fiber surface, increase their binding force, prevent the nanoparticles from falling off, and improve durability.
[0039] Embodiment 3
[0040] Add 2L of deionized water to a container, and mix 0.5% household detergent and 15% ethanol to form a uniform degreasing solution; immerse the cotton fiber in the degreasing solution at 60°C, stir at 200rpm for 60 minutes, and take it out and dry it at 80°C for 2 hours. Take another container and add 2L of deionized water, mix 2% ammonia water and 2% hydrogen peroxide to form a surface activation solution, immerse the degreased fiber in it and heat it to 50°C, put the beaker into an ultrasonic cleaning machine, and perform ultrasonic treatment at a frequency of 50kHz for 15 minutes; after taking it out, rinse it in deionized water 3 times, 10 minutes each time, to remove residual chemicals, and then dry the activated fiber at 80°C for 2 hours to ensure that the fiber surface is completely dry and activated. Place the cleaned and dried fiber substrate into the vacuum chamber of the plasma treatment equipment to ensure that the fibers are evenly distributed and not overlapped; start the vacuum system, reduce the pressure in the vacuum chamber to 13Pa, introduce oxygen into the vacuum chamber, and the gas flow rate is 100 cubic centimeters / minute; start the plasma generator with a power of 100w, and treat for 20 minutes to increase the chemical activity of the fiber surface. Take tetraethoxysilane and dissolve it in ethanol at a concentration of 5%, add 2L deionized water, 3% ammonia water, and S3 treated fiber in sequence, stir the solution for 60 minutes, filter, collect the fiber, and dry the fiber at 50°C to obtain nano-silica modified fiber. Take aluminum nitrate and dissolve it in water at a concentration of 5%, then add nano-silica modified fiber to the solution, heat the solution to 60°C, and stir continuously to promote the hydrolysis of aluminum ions. After reacting for 3 hours, filter, collect the fiber, and dry the fiber at 50°C to obtain nano-alumina modified fiber. Take 1% of the silane coupling agent and dissolve it in anhydrous ethanol. Add a pH adjuster to adjust the pH to 5 to promote the hydrolysis and reaction of silane. Put the fiber that has been treated with in-situ growth into the silane coupling agent solution to ensure that the fiber is completely immersed. Control the temperature at 50°C and soak for 24 hours. After soaking, take out the fiber and rinse it with plasma water to remove the residual silane coupling agent. Curing at 150°C for 24 hours to enhance the chemical bonding between the silane coupling agent and nano-silica, and obtain modified fiber. Scanning electron microscopy was performed on the fiber before and after modification with silane coupling agent. The test results are as follows: Figure 5 , 6 As shown, the silane coupling agent can form a strong chemical bond between the nanoparticles and the fiber surface, increase their binding force, prevent the nanoparticles from falling off, and improve durability.
[0041] Embodiment 4
[0042] The fabric samples obtained by weaving the fibers of Examples 1, 2, and 3 and ordinary commercially available flame-retardant fabrics were cut into sizes of 300mm×100mm and fixed horizontally on the combustion tester to ensure that the samples remain stable during the test. A 20mm high propane flame was contacted to the bottom of the four samples for 10 seconds, and key data such as the flame spread time, burning length, smoldering time, and extinction time during the combustion process were recorded. The time of whether the fabric continues to burn or extinguishes after the flame is evacuated was recorded, the carbonization length of the fabric and whether molten droplets occurred were recorded, and the highest temperature of the sample surface during the combustion process was recorded by a temperature sensor. The test results are shown in the following table.
[0043]
[0044] This patented fabric performs well in key indicators such as flame spread time, smoldering, self-extinguishing, and carbonization length, and is significantly better than ordinary commercially available flame-retardant fabrics. The experimental results further verify the high flame retardant properties and greater safety of this patented fabric, and it is suitable for protective equipment and functional textiles in high-risk, high-temperature environments.
[0045] Embodiment 5
[0046] The fabric samples obtained by weaving the fibers of Examples 1, 2, and 3 and ordinary commercially available fabrics were cut into pieces with a size of 300 mm × 300 mm. The samples were placed between an ultraviolet light source and an ultraviolet spectrometer. The ultraviolet light source was used to simulate sunlight irradiation in the wavelength range of 200 to 400 nm, and the ultraviolet transmittance was recorded. Figure 7 As shown. Through the introduction of nano-silicon dioxide, this patented fabric has excellent anti-ultraviolet performance and can effectively protect more than 98% of ultraviolet rays. Through comparative experiments, this patented fabric is far superior to ordinary commercially available fabrics in terms of anti-ultraviolet function. It is particularly suitable for outdoor protection and high ultraviolet exposure environments, providing users with stronger skin protection.
[0047] Embodiment 6
[0048] The fabric samples obtained by weaving the fibers of Examples 1, 2, and 3 and the common commercially available fabrics were cut into pieces with a size of 300 mm × 300 mm, and the reflectivity of the samples in the 7-14 micron band was measured using an infrared spectrometer, with a focus on this band because it is the main band for heat dissipation by radiation from the earth's surface and the human body. The samples were placed in an environmental control box, irradiated with a simulated solar light source, and the surface temperature change of the fabric within 30 minutes was measured and recorded, and the results are shown in the following table.
[0049]
[0050] Conclusion: The infrared reflectivity of this patented fabric is significantly higher than that of ordinary commercially available fabrics, which means that it can reduce heat absorption by reflecting infrared rays, making it more suitable for use in high temperature environments and providing a passive cooling effect.
[0051] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A composite flame retardant fabric, characterized in that: The composite flame-retardant fabric is composed of 40-60 parts of modified fiber, 30-40 parts of polyester fiber, 15-20 parts of viscose fiber, 15-20 parts of nylon fiber and 20-30 parts of carbon fiber by weight. The preparation method of the modified fiber comprises the following steps: S1 Add 1~2L of deionized water into a container, and mix with 0.3~0.5% household detergent and 10~15% ethanol to form a uniform degreasing solution; immerse the cotton fiber in the degreasing solution at 50~60℃, stir at 150~200rpm for 30~60 minutes, take out and dry at 60~80℃ for 1~2 hours; S2 Take another container and add 1~2L of deionized water, mix 1~2% ammonia water and 0.5~2% hydrogen peroxide to form a surface activation solution, immerse the degreased fiber in it and heat it to 40~50℃, put the beaker into an ultrasonic cleaning machine, and perform ultrasonic treatment at a frequency of 40~50kHz for 10~15 minutes; after taking it out, rinse it in deionized water for 2~3 times, each time for 5~10 minutes to remove residual chemicals, and then dry the activated fiber at 70~80℃ for 1~2 hours to ensure that the fiber surface is completely dry and activated; S3 Place the cleaned and dried fiber substrate into the vacuum chamber of the plasma treatment equipment to ensure that the fibers are evenly distributed and do not overlap; start the vacuum system, reduce the pressure in the vacuum chamber to 1~13Pa, introduce oxygen into the vacuum chamber with a gas flow rate of 10~100 cubic centimeters / minute; start the plasma generator with a power of 10~100w, and treat for 5~20 minutes to increase the chemical activity of the fiber surface; S4: dissolving tetraethoxysilane in ethanol at a concentration of 2-5%, sequentially adding 1-2 L of deionized water, 1-3% ammonia water, and the fiber treated with S3, stirring the solution for 30-60 minutes, filtering, collecting the fiber, and drying the fiber at 40-50°C to obtain nano-silica modified fiber; S5: dissolving aluminum nitrate in water to a concentration of 2-5%, adding nano-silica modified fiber to the solution, heating the solution to 50-60°C, and stirring continuously to promote the hydrolysis of aluminum ions. After reacting for 1-3 hours, filtering, collecting the fiber, and drying the fiber at 40-50°C to obtain nano-alumina modified fiber; S6 Take 0.5~1% of silane coupling agent and dissolve it in anhydrous ethanol, add pH adjuster to adjust pH to 4~5 to promote hydrolysis and reaction of silane; put the fiber after in-situ growth treatment into the silane coupling agent solution to ensure that the fiber is completely immersed, control the temperature at 40~50℃ and soak for 12~24 hours; after soaking, take out the fiber and rinse it with plasma water to remove residual silane coupling agent, and cure it at 120~150℃ for 12~24 hours to enhance the chemical bonding between the silane coupling agent and nano-silica to obtain modified fiber.
2. A composite flame retardant fabric as claimed in claim 1, characterized in that: The nano-silica particle size on the surface of the nano-silica modified fiber described in S4 is 10 to 50 nanometers.
3. A composite flame retardant fabric as claimed in claim 1, characterized in that: The particle size of the nano-alumina on the surface of the nano-alumina modified fiber described in S5 is 10 to 30 nanometers.
4. The composite flame retardant fabric according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane.
5. The composite flame retardant fabric according to claim 1, characterized in that: The pH adjuster is acetic acid.
6. A method for preparing a composite flame-retardant fabric according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1 According to the formula ratio, weigh the modified fiber, polyester fiber, viscose fiber, nylon fiber and carbon fiber respectively, add the weighed fibers into the high-speed mixer in turn, and stir them by mechanical stirring for 5 to 10 minutes to ensure that the fibers are initially evenly distributed; S2 The preliminarily mixed fibers are subjected to secondary mixing through a cotton opener for 15 to 30 minutes; S3 The mixed fibers can be treated with slight pressure to form a fixed fiber sheet, which is convenient for subsequent processing; S4 Store the shaped fiber in a dry environment to avoid moisture or pollution to ensure the stability of fiber performance.